Home-based businesses: Issues and problems with specific reference to Bloemfontein - Juries-Whiteman, RC; Campbell, Malene (Acta Structilia, 2001)
There is a high occurrence of home-based businesses in Bloemfontein (Free State) and in other cities and towns in South Africa. With the new role of local authorities as ’developmental local government’ and their responsibility for local economic development, home-based businesses may be revised and a fresh, integrated approach be followed to assist in writing a new policy for improving the ability of such enterprises to contribute towards the local economy in Bloemfontein. The Bloemfontein Town Planning scheme (no l of 1954) with its high standards of land use, is not the ideal management document of land use to stimulate home-based development. Contrary to this, Annexure F of the Black Communities Development Act that is still used to control development of land use in Mangaung, makes provision for the use of a portion of a residential property for business purposes without applying for the approval of the local council. Annexure F is therefore a far less sophisticated scheme, with less participation and rudimentary protection of rights.